RETRACTION NOTICE TO “Examining Senior High School Teachers’ Per-ceived Readiness in Online Teaching” - Santillan Jr., Eduardo P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This article entitled “Examining Senior High School Teachers’ Perceived Readiness in Online Teaching” (2023), authored by Eduardo P. Santillan Jr, published in Vol. 4, No. 2 of International Journal of Multidisciplinary: Applied Business and Education Research. 4(2), 487 – 500 has been retracted as requested by the authors.